HUBUNGAN HUKUM KONTRAK ELEKTRONIK DENGAN KEAMANAN TRANSAKSI DIGITAL - Opik Sepriadi; Pandri Zulfikar; Salman Al Ghifari; Unggul Budi; Ridwan (Berajah Journal, 2026)
The development of information and communication technology has encouraged the transformation of conventional transaction systems into electronic-based digital transactions. In modern business practices, electronic contracts have become the main legal instrument used in various digital trade activities, including e-commerce, financial technology, digital banking services, and cross-border transactions. However, the increasing use of electronic contracts also raises various legal issues related to digital transaction security, personal data protection, party authentication, validity of electronic evidence, and cybercrime risks. This study aims to analyze the legal relationship between electronic contracts and digital transaction security from the perspective of Indonesian positive law. The research method used is normative legal research with statutory and conceptual approaches. Sources of legal materials were obtained from laws and regulations, legal doctrines, scientific journals, and relevant court decisions. The results show that electronic contracts have valid legal force as long as they fulfill the legal requirements of agreements as regulated in Article 1320 of the Indonesian Civil Code and the provisions of the Electronic Information and Transactions Law. Digital transaction security is an important element in ensuring legal certainty, consumer protection, and public trust in electronic systems. Therefore, strengthening regulations, improving cybersecurity systems, and harmonizing digital laws are necessary to create a secure, fair, and sustainable electronic transaction ecosystem.